2006
DOI: 10.1080/09513590600645767
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen receptor polymorphisms in tamoxifen-treated women with breast cancer

Abstract: In postmenopausal women with estrogen receptor (ER)-positive breast cancer, long-term tamoxifen administration has proved beneficial after surgical treatment and subsequent chemotherapy. One of the major adverse effects of tamoxifen is the development of endometrial pathology (polyps, endometrial hyperplasia and endometrial cancer). PvuII and XbaI polymorphisms of the estrogen receptor-alpha gene (ERalpha) and RsaI and AluI polymorphisms of the estrogen receptor-beta gene (ERbeta) have been associated with bre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Our panel included two often studied SNPs (rs1256049 [RsaI] and rs4986938 [AluI]), previously examined in relation to cancer at various sites, including colon or rectum [10], endometrium [23], ovary [24], prostate [9, 25, 26], and breast [1114, 16, 27, 28], though implicated only in rectal (rs1256049 (RsaI); [10]) and breast cancer (rs4986938 (AluI); [12]). Though rs1256049 [RsaI] showed moderate linkage with rs1256061 (r 2 =0.55), differences in lung tumor ERβ expression in relation to rs1256049 [RsaI] were not statistically significant (Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…Our panel included two often studied SNPs (rs1256049 [RsaI] and rs4986938 [AluI]), previously examined in relation to cancer at various sites, including colon or rectum [10], endometrium [23], ovary [24], prostate [9, 25, 26], and breast [1114, 16, 27, 28], though implicated only in rectal (rs1256049 (RsaI); [10]) and breast cancer (rs4986938 (AluI); [12]). Though rs1256049 [RsaI] showed moderate linkage with rs1256061 (r 2 =0.55), differences in lung tumor ERβ expression in relation to rs1256049 [RsaI] were not statistically significant (Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…Because of the phenotypic prevalence of the wild-type allele, the heterozygotes do not express the polymorphism. The Pvu II and Xba I polymorphisms of the ERα gene and the RsaI and Alu I polymorphisms of the ERβ gene have been associated with breast cancer [19,20] and other tumors [21]. The homozygosity of the polymorphic-type alleles showed that the a alleles were more frequent in the melanoma group than in the control group, with proportions of 43.8 and 39.5%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…SNPs have been identified in the two genes encoding ERs, ESR1 and ESR2 (encoding ERα and ERβ, respectively), which alter their expression (3). Most studies of ER SNPs have focused on their roles in breast cancer (12), osteoporosis (13) and prostate cancer (14). However, little information exists to describe the role of ER polymorphisms in unexplained infertility.…”
Section: Discussionmentioning
confidence: 99%